2014
DOI: 10.1051/matecconf/20141501013
|View full text |Cite
|
Sign up to set email alerts
|

Facilities Management Service Delivery in Public and Private High Rise Residential Buildings in Nigeria: A case study of Eko Court Complex and Niger Towers

Abstract: Abstract. This study assessed and compared the delivery of Facilities Management (FM) services in public and private high rise residential buildings in Lagos, Nigeria. While some facilities or services may not be available in some public estates, the efficiency of the available ones is inadequate in comparison with the adequacy and efficiency of services provided in private estates. The objectives set for the study include identification of services that are provided in the case studies, service delivery metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, findings in a study by Zawawi et al (2013) identified that the number 3 ranked non-core facilities which are frequently outsourced or contracted-out by the organisation is landscape services, whereas number one and two were ranked for waste management and security and safety respectively. In the meantime, in Nigeria, most facilities services in high-rise buildings for residential are being outsourced to a standard Service Level Agreement, for instance, sewage treatment, lift management, the swimming pools, and also internet or (Digital Satellite Television) DSTV system as these services require relevant professionals (Olanrele et al, 2013). However, a review by Mohd.Nur & Musa (2017) informed that majority of the shopping centres in Klang Valley prefer to still practice in-house maintenance procurement strategy for most of the non-core activities.…”
Section: Maintenance Procurement Strategymentioning
confidence: 99%
“…Furthermore, findings in a study by Zawawi et al (2013) identified that the number 3 ranked non-core facilities which are frequently outsourced or contracted-out by the organisation is landscape services, whereas number one and two were ranked for waste management and security and safety respectively. In the meantime, in Nigeria, most facilities services in high-rise buildings for residential are being outsourced to a standard Service Level Agreement, for instance, sewage treatment, lift management, the swimming pools, and also internet or (Digital Satellite Television) DSTV system as these services require relevant professionals (Olanrele et al, 2013). However, a review by Mohd.Nur & Musa (2017) informed that majority of the shopping centres in Klang Valley prefer to still practice in-house maintenance procurement strategy for most of the non-core activities.…”
Section: Maintenance Procurement Strategymentioning
confidence: 99%
“…Ref. [6] carried out a comparative study on the delivery of facility management services between publicly and privately owned high-rise residential buildings in Lagos. Residents of the selected high-rise buildings (Eko Court complex and Niger Towers) were sampled.…”
Section: Concept Of Facility Managementmentioning
confidence: 99%
“…Furthermore, it has been shown that in industrialized nations, forecasting, budgeting, and building operations and maintenance are all impacted by facility management automation [4]. Studies on high-rise buildings in Nigeria have centered on construction, maintenance, and the impact on the economy [5][6][7][8]. There has not been extensive research on facility management automation as an option for building owners and facility managers of high-rise buildings in Nigeria to ensure the sustainability of investors' investment in landed properties.…”
Section: Introductionmentioning
confidence: 99%